Mechanism of Action of Copper Ion on the Activity of Protein Tyrosine Phosphatase PTP1B and Its Toxicological Activity. (20th July 2015) - Ha, Siyong; Kim, Da Young; Min, Bum Hong; Ham, Seung Wook
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10376-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>